2018
DOI: 10.1002/jbio.201800145
|View full text |Cite
|
Sign up to set email alerts
|

In vivo estimation of water diffusivity in occluded human skin using terahertz reflection spectroscopy

Abstract: Water diffusion and the concentration profile within the skin significantly affect the surrounding chemical absorption and molecular synthesis. Occluding the skin causes water to accumulate in the top layer of the skin (the stratum corneum [SC]) and also affects the water diffusivity. Scar treatments such as silicone gel and silicone sheets make use of occlusion to increase skin hydration. However with existing techniques, it is not possible to quantitatively measure the diffusivity of the water during occlusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…However, by using more complex optical models we can obtain more information about the sample. For example, stratified media theories can be used to consider skin as a multilayered structure [23,24] and be used to extract information about the different sample layers. Since research has shown that skin has a water concentration gradient [23,25], a more accurate model would take into account how the water concentration changes at different depths.…”
Section: Thz Skin Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by using more complex optical models we can obtain more information about the sample. For example, stratified media theories can be used to consider skin as a multilayered structure [23,24] and be used to extract information about the different sample layers. Since research has shown that skin has a water concentration gradient [23,25], a more accurate model would take into account how the water concentration changes at different depths.…”
Section: Thz Skin Modelsmentioning
confidence: 99%
“…In order to understand the mechanical deformation of skin under different pressures, we used the model in the above paragraph to calculate the reflectivity (Rcal in Eq. (5)) then fit to our measured reflectivity results Rmeas [23,24] to evaluate how the various skin parameters change under different pressures. The fitting parameters of our proposed model, shown in blue in Fig.…”
Section: Thz Skin Modelsmentioning
confidence: 99%
“…Guo et al showed how a coherent THz holography system can be used to understand the dehydration dynamics of pork, mutton and cattle tissue [9]. Furthermore, THz spectroscopy has been used in conjunction with water diffusion models to estimate the reflectivity of occluded human skin [10,11]. Therefore, THz Time-Domain Spectroscopy (THz-TDS) and imaging are promising tools for probing the water content of in vivo and ex vivo biological tissue.…”
Section: Introductionmentioning
confidence: 99%
“…During in vivo measurements, the pressure between the imaging window and the skin area of interest affects the THz signal as the skin becomes compressed at higher pressures [17]. Additionally, contacting the imaging window blocks the pores on the skin, causing occlusion [18]. The reflected THz signal is very sensitive to the changes in hydration caused by occlusion.…”
Section: Introductionmentioning
confidence: 99%